Automatic Plant Watering Using a Real-Time Soil Moisture Sensor Based on the Internet of Things at STMIK Kaputama - Rendi, Rendie (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
Plant watering is an important aspect of agriculture, but manual methods are often inefficient. This research aims to design and implement an Internet of Things (IoT)-based automatic watering system using a soil moisture sensor. This system measures humidity in real-time and automatically controls the water pump based on a specified threshold. When humidity is <65%, the pump will be active, and when humidity is between 65%-80%, the pump will be off. The main hardware is an ESP32, a soil moisture sensor, a relay, and a water pump, while monitoring is carried out through the Blynk application. Test results show that the system is able to work according to the expected control logic, increasing watering efficiency and reducing water waste. This system is effectively implemented on a small scale such as the campus garden at STMIK Kaputama.